Adjustable vena cave mounting system - GAO ZHIKANG (2015)
The utility model discloses an adjustable vena cave mounting system, including inferior vena cava support (1), connection steel cable (2), push rod (3) and transport sheath (4), the landing leg (1 -1) of inferior vena cava support (1) head end is threaded connection with the head end (2 -1) of being connected steel cable (2), and connection steel cable (2) tail end is equipped with turns round accuse ware (2 -2), and the three forms one set of adjustable delivery system jointly, push rod (3) lateral wall is equipped with and is connected recess (3 -1), the afterbody that steel cable (2) diameter matches and is equipped with adjustable bolt (3 -2), the utility model discloses but the support not totally before the release radiography observe the support position, if the dissatisfied recoverable support in support position, relocalisation release, support release position's accuracy in providing the blood vessel that lasts in the holding power, is guaranteed to the effectual skip before effect of having eliminated when the support releases totally simultaneously, has guaranteed treatment, has improved the security of operating.